Hyperopia-Correcting Phototherapeutic Keratectomy and Its Comparison With Conventional Phototherapeutic Keratectomy - Hayakawa, Hideki; Kamiya, Kazutaka; Tsujisawa, Tatsuhiko; Takahashi, Masahide; Shoji, Nobuyuki (Frontiers in Medicine, 2022)
PURPOSE: To evaluate hyperopia-correcting phototherapeutic keratectomy (HC-PTK) and to compare the visual and refractive outcomes of HC-PTK and conventional PTK. METHODS: This study comprised a total of 72 eyes of 72 consecutive patients who underwent HC-PTK and conventional PTK for granular corneal dystrophy or band-shaped keratopathy. Preoperatively and 6 months postoperatively, we assessed visual acuity, manifest refraction, and mean keratometry, as well as postoperative corneal higher-order aberrations and adverse events in each PTK group, and compared these metrics between the two groups. RESULTS: LogMAR BSCVA significantly improved from 0.43 ± 0.47 preoperatively to 0.21 ± 0.38 postoperatively in the HC-PTK group (Wilcoxon signed-rank test, p<0.001). It was also significantly improved from 0.22 ± 0.21 preoperatively to 0.15 ± 0.12 postoperatively in the conventional PTK group (p=0.031). Mean refraction significantly changed from 0.27 ± 1.55 diopter (D) preoperatively to 0.50 ± 1.77 D postoperatively, in the HC-PTK group (p=0.313). By contrast, it was significantly hyperopic from -0.15 ± 2.41 D preoperatively to 1.45 ± 2.46 D postoperatively, in the conventional PTK group (p<0.001). No significant complications occurred in any case during the follow-up period. CONCLUSIONS: Both HC-PTK and conventional PTK showed a significant improvement of BSCVA and no vision-threatening complications at any time in this series. HC-PTK significantly reduced a hyperopic shift in refraction compared with conventional PTK, suggesting its viability for patients requiring PTK, especially in consideration of preventing this hyperopic issue.